Relationship between ring-width growth of Pinus kesiya royle ex Gordon and climatic factors in the Duc Trong area of Lam Dong province - Van Cuong, Le (Journal of Forestry Science and Technology, 2025)
The paper presented the study results on the response of Pinus kesiya Royle ex Gordon to variations in climatic variables in the Duc Trong area of Lam Dong province. This study was carried out to identify the key climatic factors that significantly influence the ring-width growth of P. kesiya. The research data included series of P. kesiya ring widths from 1905 to 2014 and climatic data from 1980 to 2014. The relationship between the ring-width growth of P. kesiya and climatic parameters was determined using Pearson correlation coefficients. The role of climatic factors on the ring-width growth of P. kesiya was analyzed using stepwise multivariate linear response Equations. The results showed that: (1) The increase in temperature in September and October, precipitation in March and total precipitation in November, and December, sunshine hours in November, and hydrothermal coefficient in June all led to a decrease in the growth of P. kesiya. (2) On the contrary, the high air humidity during the dry season from January to April was a favorable condition for the growth of P. kesiya. (3) The four strongest controlling parameters for the growth of P. kesiya were total precipitation in November and December, air humidity during January to April, hydrothermal coefficient in June and air temperature in September.